Statin: A boon in periodontal therapy - Sahana Purushotham; Melba Lisa D'Souza; Ramaiah Purushotham (Wolters Kluwer Medknow Publications, 2015)
Periodontitis is an inflammatory process causing gradual destruction of the periodontal tissues and alveolar bone loss. Various periodontal therapies have been introduced to lower the destruction, statin being one among them. They are cholesterol-lowering drugs which promote bone formation, hence proven to be effective in periodontal therapy. This article reviews the effects of statin and examines its potential role in periodontal regenerative therapy.